2020
DOI: 10.2147/jaa.s272850
|View full text |Cite
|
Sign up to set email alerts
|

<p>Childhood Asthma Awareness in Saudi Arabia: Five-Year Follow-Up Study</p>

Abstract: Background: Bronchial asthma is a chronic inflammatory airway disease that is characterized by reversible airway obstruction due to bronchial hyperresponsiveness. It is one of the most common chronic diseases. In Saudi Arabia, asthma affects 2 million people with asthma frequency in children markedly higher than adults with regional variations ranging from 9% to 33.7%. Objective: The aim of this study is to measure asthma awareness and knowledge of study participants during the ongoing annual Saudi asthma awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
(40 reference statements)
0
11
1
Order By: Relevance
“…When compared to previous studies we found that the knowledge about using inhaler technique has risen in our study compared with other studies [7,20]. Also the information public about from where to get information has increased, in the study conducted in Jeddah, Riyadh, and Dammam, during the National Asthma Awareness Campaign in April 2019 [21], only 22% of the participants get their information from their doctor wherein our study 139 (77.2%) of the participants tend to get their information from their primary doctor, and this indicates a better awareness and better treatment outcomes, as well as this, will assure that the patients will comply to medication and deliver the drug in the most effective way and technique.…”
Section: Discussioncontrasting
confidence: 43%
“…When compared to previous studies we found that the knowledge about using inhaler technique has risen in our study compared with other studies [7,20]. Also the information public about from where to get information has increased, in the study conducted in Jeddah, Riyadh, and Dammam, during the National Asthma Awareness Campaign in April 2019 [21], only 22% of the participants get their information from their doctor wherein our study 139 (77.2%) of the participants tend to get their information from their primary doctor, and this indicates a better awareness and better treatment outcomes, as well as this, will assure that the patients will comply to medication and deliver the drug in the most effective way and technique.…”
Section: Discussioncontrasting
confidence: 43%
“…Figure (1) illustrates that none of the males were low, 32(54.2%) were moderate, 27(45.8%) were high, 2(1.7%) of females were low, 36(31%) were moderate, 78(67.2%) were high, 2(1.1%) of the total were low, 68(38.9%) were moderate, 105(60%) were high, and there is a statistical relation between the level of awareness among males and females regarding complications of bronchial asthma.…”
Section: Resultsmentioning
confidence: 99%
“…Such considerable differences in the results of epidemiological studies are most likely due to the complex definition of the disease and the difficulties in its diagnosis [ 1 , 4 ]. In China there are 45.7 million people (4.2%) affected with asthma, whereas in Saudi Arabia the number of asthma patients is approximately 2 million, which is 6% of the country’s general population [ 8 , 9 ]. In our study, which evaluated a population of 18,617 people, asthma was diagnosed in 2,508 (13.4%) people, including 1,272 (12.7%) women and 1,236 (14.4%) men.…”
Section: Discussionmentioning
confidence: 99%